Portuguese Enlightenment and Public Instruction: the contributions of Antonio Ribeiro Sanches to educational assumptions in the second half of the eighteenth century (Research, Society and Development, 2018)
The second half of the eighteenth century in Portugal was a time of several changes for the kingdom and its colonies. The formulation of works debating education in the kingdom, the contributions of the Enlightenment and the rise of the Marquis of Pombal, mark some of the transformations that changed the administration of the kingdom and, consequently, the pedagogical scenario of the metropolis and its possessions. With the collaboration of Antônio Ribeiro Sanches, considered one of the Portuguese Enlightenment, and his work "Letters on Education of the Mocidade", the educational scene in the Portuguese metropolis undergoes changes that promote a new conception of public instruction and civility. The purpose of this article is to discuss the civilizing process, specifically analyzing the contributions of the Portuguese Enlightenment to the Pombaline Reforms of Education and investigating the changes in the educational system in the Northern Capitanias. Theoretically we will be guided by the German sociologist Norbert Elias, thinking education as a condition in which men have become civilized in a historical teaching-learning process that has also become essential to the so-called development of manners and behaviors responsible for the formation of a model of civilization, both in the Metropolis and in the colonies of America. As a methodological proposal, we approach the perspective of the Social History of Knowledge of the English historian Peter Burke, for analyzing the work of the Portuguese philosopher will analyze the practice, reception and behavior of the educational presuppositions of the Portuguese Enlightenment. From the analysis of Antônio Ribeiro Sanches we verified a modernizing and civilizing process in education.